Sistem Pendukung Keputusan Pemilihan Calon Tenaga Kerja Terbaik Menggunakan Metode MOORA - Hayu Yusnaini; Katen Lumbanbatu; Siswan Syahputra (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The Department of Manpower and Trade Industry is a government agency in Binjai City that has a role in developing the skills of prospective workers who have expertise and work quality. A company can develop well influenced by the quality of the workforce Manpower is an important part in carrying out company operations. What is currently happening is that the Department of Manpower and Industry and Trade of Binjai City has difficulties in selecting the best and most competent workforce according to the needs of the company. Taking this into account, a decision support system is needed that can function as a selector for each workforce with predetermined criteria. By using a decision support system, the selection of the best workforce will be faster and more efficient. One of the methods in decision selection is Multi Objective Optimization on The Basis of Ratio Analysis (MOORA). MOORA is one that can perform calculations on the value of attribute criteria that help decision makers to make the right decisions.